Chemical and Microbiological Assessment of Wastewater Discharged along the Mediterranean Sea - Hassen, Wafa; Mehri, Ines; Beltifa, Asma; Giorgia Potortì, Angela; Khellaf, Nabila; Amer, Ranya; Van Loco, Joris; Hassen, Abdennaceur; Di Bella, Giuseppa; Khdary, Nezar H.; Ben Mansour, Hedi (Sustainability, 2022)
The large discharges of wastewater in different natural receiving environments, particularly the marine environment, have massively contributed to pollution. This study examined the physicochemical and microbiological quality of wastewater discharged along the Mediterranean Sea. This investigation is one of the few works carried out by scientists along with the Mediterranean countries. Wastewater sampling was carried out in Egypt, Morocco, Algeria, Tunisia, and Italy. Analyses confirmed that the quality of treated wastewater was always better than the ones registered as raw wastewater. In addition, the quality of the treated wastewater and seawater appeared to be adequate and satisfied the standard and recommended limits in vigor in all these Mediterranean countries. These results showed that the wastewater treatment process used in Italy allowed a higher reduction in most tested parameters (COD: 80.44%, BOD5: 58.9%, OM: 70.74%, TOC: 78.4%). The bacteriological quality of these waters and their diversification was assessed by the denaturing gradient gel electrophoresis (DGGE) technique. Firmicutes, Gamma-Proteobacteria, and Beta-Proteobacteria in 42% of the DGGE DNA bands, and predominately some lineages affiliated to cultivable and non-cultivable clones of Bacteroides (58%), were found. The examination of antibiotic susceptibility at the level of 18 strains isolated from various arbitrary water samples showed that most of these isolates exhibited resistance to at least one antibiotic family, and 11 isolates exhibited 100% resistance against aztreonam. This result confirms the large antibiotic-resistance spreading and circulation registered these last decades in the natural environment, conditioned by the extensive and non-controlled use of antibiotics for human therapy and animal feeding.